Zirk Plant Used in Medicinal and Decorative Landscaping - Abdukhamidovich, Nasritdinov Akhmadjon; Fazliddin’s, Mukhiddinova Oydinoy (American Journal of Biodiversity, 2025)
Zirk plant has been widely used as a medicinal and decorative plant since ancient times. Zirk plant is a promising plant in medicine, medicine, food industry and environmental protection. They have an important feature in cleaning the ambient air, protecting the air from pollution while enriching the decorative landscape. There are many types of zirk plant, there are also hybrid types.